2010
DOI: 10.1002/clc.20815
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Receptors for Advanced Glycation End Products (sRAGE) as a Predictor of Restenosis Following Percutaneous Coronary Intervention

Abstract: Background: Interaction of advanced glycation end products (AGEs) with their receptor (RAGE) increases expression of inflammatory mediators (tumor necrosis factor alpha [TNF-α] and soluble vascular cell adhesion molecule-1 [sVCAM-1]) and induces oxygen radicals that are implicated in atherosclerosis. Balloon-injuryinduced atherosclerosis is associated with increased expression of AGEs and RAGE. The soluble receptor for AGE (sRAGE), which acts as a decoy for RAGE ligands (AGEs), prevents atherosclerosis in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 61 publications
(41 reference statements)
3
36
1
Order By: Relevance
“…These findings were similar to other studies asserting that AGEs may be associated with either control of diabetes or complications of diabetes, and also linked them with diabetes-related complications such as atherosclerosis and restenosis after percutaneous coronary intervention [23-25]…”
Section: Discussionsupporting
confidence: 90%
“…These findings were similar to other studies asserting that AGEs may be associated with either control of diabetes or complications of diabetes, and also linked them with diabetes-related complications such as atherosclerosis and restenosis after percutaneous coronary intervention [23-25]…”
Section: Discussionsupporting
confidence: 90%
“…Although such an inverse relationship has been described in older apparently healthy adults [49], young and middle-aged subjects did not present any relationship either in our, or in an Italian study [16]. Independent clinical studies suggested that sRAGE or esRAGE could serve as novel biomarkers for estimation of the risk of progression of atherosclerotic disorders [26][27][28]44]. We might speculate that observed Metsy-associated decline in sRAGE might be driven by incipient atherosclerotic changes, and could be later on with manifestation of atherosclerosis reflected by change in CML/sRAGE ratio.…”
Section: Discussioncontrasting
confidence: 50%
“…AGEs and RAGE levels were seldom determined simultaneously. sRAGE -a novel biomarker for estimation of the risk of progression of atherosclerotic disorders [26][27][28] -might be of pathophysiological importance in feedback regulation of the toxic effects of AGE/RAGE-mediated signaling [2,20,27,28]. To elucidate whether alterations in AGE/RAGE axis appear early before manifestation of comorbidities, we investigated whether the increasing number of Metsy risk factors associates with change in circulating AGEs and sRAGE levels in young-tomiddle-aged medication-free non-diabetic subjects.…”
Section: Introductionmentioning
confidence: 99%
“…These 27 articles were published between 2004 and 2012, with 4 articles written in Chinese [22], [27], [30], [31] and the others in English. One article was grouped by ethnicity [13] and hypertension [24] respectively, three by CAD subtypes (CAD, MI, CAD with and without restenosis) [14], [17], [25], and five by diabetes mellitus [5], [8], [19], [20], [23]. These independent subgroups were treated separately, and accordingly there were 39 groups in final analyses.…”
Section: Resultsmentioning
confidence: 99%